The organisation of the educational process in the distance learning format in the frontline territories during the period of martial law in Ukraine - O. Plakhotnyk; S. Burian (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
Analysing current approaches to organising remote learning in the frontline territories of Ukraine during martial law is crucial to ensure the continuity of education in times of crisis. This study aimed to identify the main challenges and prospects of remote learning, particularly by examining international experience and evaluating the effectiveness of the implemented learning models. For this purpose, a descriptive approach involving traditional document analysis, a systematic approach, and analytical and synthetic methods was employed. The primary sources of analysis were Ukrainian Laws, resolutions, Cabinet of Ministers of Ukraine’s orders, Ministry of Education and Science orders and letters adopted after 24 February 2022. The study found that the key challenges for organising distance learning in frontline areas were ensuring the safety of participants in the educational process, a lack of technical facilities and resources, and psychological difficulties for students and teachers. The introduction of cutting-edge technologies and the adaptation of teaching methods could significantly increase the effectiveness of distance learning in times of crisis. Recommendations for enhancing the educational process have been formulated, including the integration of innovative technologies, advanced training for educators, and psychological support for all participants in the educational process. The study’s practical value lies in the potential application of these recommendations to improve the organisation of education in the frontline areas of Ukraine, ensuring the continuity of education amidst hostilities and enhancing overall educational quality. The findings can inform the development of national strategies for distance learning during crises and contribute to improving the regulatory framework in the education sector